The effects of poultry meal source on growth performance of weanling pigs - Keegan, T.P.; Hasted, C.W.; Nelssen, Jim L.; DeRouchey, Joel M.; Goodband, Robert D.; Tokach, Michael D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 350 pigs (PIC, initially 19.7 lb and 22 ± 2 d of age) was used to evaluate the effects of select menhaden fishmeal and stabilized poultry meal source on growth performance of nursery pigs. Seven dietary treatments were fed from d 4 to 19 after weaning. Diets included a control with no specialty protein products and diets with 2.5% or 5% fishmeal, or two different sources of poultry meal (low or high ash content). All the diets were formulated on an equal lysine basis. The poultry meal replaced the lysine provided by fishmeal with inclusion rates of 2.9% and 5.8% for low ash and 3.1% and 6.2% for high ash poultry meal. The low ash and high ash poultry meal sources had ash concentrations of 9% and 13%, respectively. Overall, d 0 to 15, pigs fed diets containing fishmeal or poultry meal had improved (P<0.05) F/G compared to pigs fed the control diet. Also, pigs fed low ash poultry meal had improved (P<0.05) F/G compared to pigs fed high ash poultry meal. Consistent with many previous trials, these results indicate that the addition of select menhaden fishmeal to diets improved growth performance in weanling pigs the first week and feed efficiency over a two-week period. The addition of low ash poultry meal resulted in improvements in feed efficiency, whereas high ash poultry meal did not. Based on these data, quality control specifications, such as ash content, need to be considered when using poultry meal as an animal protein replacement in diets for nursery pigs.
Keywords: Fishmeal; Poultry meal; Weanling pigs; Swine